Analsis Sektor Unggulan Dalam Mempengaruhi Pertumbuhan Ekonomi di Kabupaten Musi Banyuasin - Ayu Geby Gisela Syaputri Geby; Muhammad bahrul ulum (DIBINOM : Digital Business, Economic Jurnal, 2026)
This study aims to analyze the leading sectors that play a significant role in promoting economic growth in Musi Banyuasin Regency. The research employs the Location Quotient (LQ) method and Multiple Linear Regression analysis using data on the Gross Regional Domestic Product (GRDP) of Musi Banyuasin Regency by business field over the 2018–2024 period. The results indicate that the mining and quarrying sector serves as the basic sector in Musi Banyuasin Regency, providing the highest contribution compared to other sectors. Furthermore, seven sectors have demonstrated faster growth than those in South Sumatra Province, namely agriculture, forestry, and fisheries; mining and quarrying; electricity and gas supply; construction; accommodation and food service activities; financial and insurance activities; and health and social services. The regression estimation results show a positive relationship between leading sectors and economic growth in Musi Banyuasin Regency, implying that the enhancement of leading sectors contributes directly to the acceleration of regional economic growth.